Measuring the Root Length of Peanuts Grown in Rhizotrons Using Computer Vision - Stefanello, Leonardo Michalski; Silva, Leonardo Paillo da; Dayrell, Luís Henrique Soares; Ferrari Neto, Jayme; Pistori, Hemerson; Nucci, Higor Henrique Picoli (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão ComputacionalDO - 10.5753/wvc.2021.18901, 2021)
Peanut is one of the most grown leguminous crops in the world, but it can suffer during water deficit periods. In this paper, a new method to help monitoring root growth for laboratory experiments with this plant is proposed. By using a new combination of smoothing, thresholding, morphological filtering and skeletonization, our method has achieved a correlation of 0.968 with the Tennant's standard approach.